Reconstruction of the alveolar bone deficiency in the mandible by expansion screws - حدَاد إبراهيم; علي خليل (Latakia University Journal -Medical Sciences Series, 2024)
Objectives: The goal of this study was to evaluate the results of using the expansion screws for treatment of atrophic and deficient mandible bone. Material and Methods: A total of 6 patients (5 men and 1 woman; Age 20-36 years) who came with atrophy of alveolar bone were treated using expansion screws by horizontal distraction osteogenesis. The used device consisted of 2 parts: one was an orthodontic expander and the other was a screw-ring. The expansion screws were set on the transport bone which was osteotomized from adjacent bone and fixed to the segment using microscrews. The bone gain was gauged using radiographs (cbct). The overage of follow- up was 4 months. Results: The average of the horizontal bone gain after 4 months of the distraction osteogenesis was 7.55 mm (5.5-10). The average of the vertical bone gain after 4 months of the distraction osteogenesis was 6.91 mm (3.5-9). Conclusion: Under the limitations of this study it can be concluded that the distraction osteogenesis using expansion screws leads to reconstruction of the alveolar bone deficiency in the mandible.